PENGARUH MENYUSUI TERHADAP INVOLUSI UTERUS PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS TANGKEH KECAMATAN WOYLA TIMUR KABUPATEN ACEH BARAT - Yanti Fitriani; Evi Zahara; Sulastri Sulastri; Eva Purwita; Kartinazahari Kartinazahari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
One factor influencing the speed of the involution process is early initiation of breastfeeding. After birth, babies are able to breastfeed on their own if skin-to-skin contact is maintained between the baby and the mother for at least one hour immediately after birth. The purpose of this study was to examine the effect of breastfeeding on uterine involution in postpartum mothers in the Tangkeh Community Health Center, Woyla Timur District, West Aceh Regency. This study was an analytical survey using a cross-sectional approach. The population was 25 postpartum mothers in the Tangkeh Community Health Center, Woyla Timur District, West Aceh Regency, from January to February. The sampling technique used was total sampling. The results of this study indicate that breastfeeding affects uterine involution in postpartum mothers in the Tangkeh Community Health Center, Woyla Timur District, West Aceh Regency, with a probability value of 0.000 or <0.05. The conclusion of this study is that breastfeeding affects uterine involution in postpartum mothers in the Tangkeh Community Health Center, Woyla Timur District, West Aceh Regency. Recommendations for Health Workers: Health workers are expected to provide information regarding breastfeeding on uterine involution in postpartum mothers.